Ответ:
Пошаговое объяснение:
Нууу мне нечего говорить..
Просто подставляем вместо x число -2. Получим:
Ответ: t = -2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
Нууу мне нечего говорить..
Пошаговое объяснение:
Просто подставляем вместо x число -2. Получим:![9,5*(-2) - t = 5,7*(-2) - 5,6\\-19-t = -11,4 - 5,6\\-t = -17 + 19\\-t = 2\\t = -2 9,5*(-2) - t = 5,7*(-2) - 5,6\\-19-t = -11,4 - 5,6\\-t = -17 + 19\\-t = 2\\t = -2](https://tex.z-dn.net/?f=9%2C5%2A%28-2%29%20-%20t%20%3D%205%2C7%2A%28-2%29%20-%205%2C6%5C%5C-19-t%20%3D%20-11%2C4%20-%205%2C6%5C%5C-t%20%3D%20-17%20%2B%2019%5C%5C-t%20%3D%202%5C%5Ct%20%3D%20-2)
Ответ: t = -2